Evaluation of a personalised adherence intervention to improve photoprotection in adults with Xeroderma Pigmentosum (XP): protocol for the trial of XPAND. Issue 7 (17th July 2019) - Walburn, Jessica; Norton, Sam; Sarkany, Robert; Sainsbury, Kirby; Araújo-Soares, Vera; Morgan, Myfanwy; Canfield, Martha; Foster, Lesley; Heydenreich, Jakob; McCrone, Paul; Mander, Adrian; Sniehotta, Falko F; et al.
Abstract : Introduction: Poor adherence to photoprotection for people with xeroderma pigmentosum (XP) can be life-threatening. A randomised controlled trial (RCT) is being conducted to test the efficacy of a personalised adherence intervention (XPAND) to reduce the level of ultraviolet radiation (UVR) reaching the face, by improving photoprotection activities in adults with XP. Methods and analysis: A two-armed parallel groups RCT, where we randomised 24 patients with suboptimal adherence to either an intervention group who received XPAND in 2018 or a delayed intervention group who will receive XPAND in 2019. XPAND involves seven sessions, one-to-one with a facilitator, using behaviour change techniques and specially designed materials to target barriers to photoprotection. Following baseline assessment in April 2018 (t0) and intervention, the primary outcome will be measured across 21 consecutive days in June and July 2018 (t1). The primary outcome is the average daily UVR dose to the face (D-to-F), calculated by combining objective UVR exposure at the wrist (measured by a dosimeter) with face photoprotection activities recorded on a daily UVR protection diary. Secondary outcomes include average daily UVR D-to-F across 21 days in August (t2); psychosocial process variables measured by daily questions (t0, t1, t2) and self-report questionnaires (t0, t1, t2, December 2018 (t3)). Intervention cost-utility is assessed by service use and personal cost questionnaires (t0, t3). The delayed intervention control arm participants will complete three further assessments in April 2019 (t4) and June–July 2019 (t5), and December 2019 (t6) with dosimetry and UVR protection diary completed for 21 days at t4 and t5. A process evaluation will be conducted using mixed methods. Ethics and dissemination: Ethical approval has been received from West London & GTAC REC 17/LO/2110. Results will be disseminated in peer-reviewed journals and at conferences. This study tests a novel intervention, which, if successful, will be integrated into routine care. Trial registration number: NCT03445052; Pre-results.